Relationship between apical foramen, anatomic apex and radiographic apex in maxillary premolars - Jacobo Iván Ramos Manotas; Indira Vanesa Gómez Agudelo; Viany Mireya Ortíz Polanci; Antonio José Diaz Caballero (Editorial Ciencias Médicas, 2015)
Objective: to determine the relationship between the location of the apical foramen and the anatomic and radiographic apex in maxillary premolars. Method: a descriptive study. Samples were 106 maxillary premolars with mature apices and freshly extracted. The sampling was not probabilistic criterion. Teeth were selected according to the inclusion and exclusion criteria, access openings were made and radiographs, we measured the distance from the apical foramen and anatomic apex through the optical microscope instrument display and a slide millimeter. For data analysis tests were used descriptive statistics and the Chi2 test. Statistical significance level was set at p < 0.05. Results: it was found that the radiographic apex was 67 % in an apical position, also, the anatomic apex by 50 % in the same position. The apical foramen was found in 51 % compared to the anatomic apex. 30 teeth matched the position of the foramen and anatomical apex and 11 apical teeth have an apical position of the distal anatomic apex and apical foramen. As for the relationship of the position of the anatomical apex 48 and radiographic apex of the teeth coincide evaluated in the distal apical and 19 with a p < 0.05. Conclusion: according to data obtained in this study, we can say there is a relationship between the anatomical position of the apex and apical foramen which must be taken into account by the dentistry and the specialist during establishing the length of work in bicuspid teeth.